Reconstructing The Paradigm Of Legal Protection Of Workers: Conceptual Renewal Of Termination In The Welfare Perspective - Husaeri; Nur Mohamad Kasim; Weny Almoravid Dungga (Ajudikasi: Jurnal Ilmu Hukum, 2025)
The reform of the termination of employment (PHK) regulation in Indonesia through Law Number 6 of 2023 concerning Job Creation has had a significant impact on the legalprotection and welfare of workers. This study aims to evaluate changes in layoff regulations, the implications of compensation reductions, and the implementation of Pancasila principles and Human Rights (HAM) in the protection of workers who experience layoffs. The normative-juridical method is used by reviewing legislation, Court decisions, and the latest legal literature. The results show that although the job creation law provides flexibility for employers, the looser provisions in layoffs have the potential to harm workers, especially in the aspects of compensation and legal certainty. The implementation of Pancasila and human rights principles is an important foundation in ensuring the protection of workers so that the right to work, social justice, and humanity are maintained. Social security policies and fair dispute resolution mechanisms are strengthened through the latest Ministry of labor regulations, but the effectiveness of their implementation needs to be constantly monitored. The study recommends comprehensive reforms that promote a balance of interests between workers and employers, as well as strengthening constitutional protections for the sustainable welfare of workers.